A STUDY ON ENTREPRENEURIAL PROFILE AND PROBLEMS OF HOUSE MESS OF KOTA CITY (International Journal of Food and Nutritional Sciences, 2022)
The study aims to highlight the entrepreneurial profile of house mess and challenges/problems faced by mess entrepreneurs in Kota city. The study was conducted in Kota City Rajasthan. A sample of 200 house mess entrepreneur’s respondents who are engaged in an enterprise at the individual level and running successfully. Four areas Kunhadi, Dadawadi, Rajeev Gandhi Nagar and Vigyan Nagar have been selected randomly for study purposes. The research is based on secondary and primary data. It is exploratory and descriptive. A structured questionnaire was used to interview the respondents. Data is analyzed by frequency and percentage.